Natural history of multiple system atrophy in the USA: a prospective cohort study. Issue 7 (July 2015) - Low, Phillip A; Reich, Stephen G; Jankovic, Joseph; Shults, Clifford W; Stern, Matthew B; Novak, Peter; Tanner, Caroline M; Gilman, Sid; Marshall, Frederick J; Wooten, Frederick; Racette, Brad; Chelimsky, Thomas; et al.
Summary Background Multiple system atrophy is a rare, fatal neurodegenerative disorder with symptoms of autonomic failure plus parkinsonism, cerebellar ataxia, or both. We report results of the first prospective natural history study of multiple system atrophy in the USA, and the effects of phenotype and autonomic failure on prognosis. Methods We recruited participants with probable multiple system atrophy—of either the parkinsonism subtype (MSA-P) or the cerebellar ataxia subtype (MSA-C)—at 12 neurology centres in the USA specialising in movement or autonomic disorders. We followed up patients every 6 months for 5 years and assessed them with the Unified Multiple System Atrophy Rating Scale part I (UMSARS I; a functional score of symptoms and ability to undertake activities of daily living), UMSARS II (neurological motor evaluation), and the Composite Autonomic Symptoms Scale (COMPASS)-select (a measure of autonomic symptoms and autonomic functional status). We assessed potential predictors of outcome. We used Cox proportional hazards models to calculate univariate hazard ratios for shorter survival using age at disease onset as a continuous variable and sex, clinical phenotype, and early development of neurological and autonomic manifestations as categorical variables. Findings We recruited 175 participants. Mean age at study entry was 63·4 years (SD 8·6). Median survival from symptom onset was 9·8 years (95% CI 8·8–10·7) and median survival from enrolment was 1·8 years (0·9–2·7). Participants with severe symptomatic autonomic failure (symptomatic orthostatic hypotension, urinary incontinence, or both) at diagnosis (n=62) had a worse prognosis than those without severe disease (n=113; median survival 8·0 years, 95% CI 6·5–9·5 vs 10·3 years, 9·3–11·4; p=0·021). At baseline, patients with MSA-P (n=126) and MSA-C (n=49) had much the same symptoms and functional status: mean UMSARS I 25·2 (SD 8·08) versus 24·6 (8·34; p=0·835); mean UMSARS II 26·4 (8·8) versus 25·4 (10·5; p=0·764); COMPASS-select 43·5 (18·7) versus 42·8 (19·6; p=0·835). Progression over 5 years, assessed by change in UMSARS I, UMSARS II, and COMPASS-select, was modest. Interpretation Probable multiple system atrophy is a late-stage disease with short survival. The natural histories of MSA-P and MSA-C are similar and severe symptomatic autonomic failure at diagnosis is associated with worse prognosis. Funding US National Institutes of Health, Mayo Clinic, and Kathy Shih Memorial Foundation.